(untitled) (Annual of the Faculty of Philosophy in Skopje, 2009)
The article discusses the differences between the advocates of quantitative method and those oriented towards the qualitative approaches in the domain of psychology. The author explains the assumptions that generate opposite views among the two methodological campuses regarding the issue of generalizing, as well as concerning the implications of its (mis)use upon the policies that regulate human relations. Finally, the alternative strategies for generalizing are presented. It is believed that these strategies brings together the two methodological approaches by making the certainty of generalization among the quantitative methodologists being less absolute and by recognizing the importance of generalizing for the intervening processes among the qualitative methodologist.